Kemampuan Berpikir Kritis Matematis di Indonesia: Sistematik Literatur Reviu (SLR) - Elmawati Elmawati; Dadang Juandi (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
Mathematical critical thinking ability is one of the skills contained in 4C competencies that 21st-century students must possess. Many studies related to mathematical critical thinking skills have been carried out. The purpose of this research is to find out how the heterogeneity of studies related to the analysis of mathematical critical thinking skills in Indonesia based on the year of publication, education level, grade level, publication in journals indexed by sinta, the subject matter used in research, demographics, and indicators of critical thinking ability. The method used in this study is a Systematic Literature Review (SLR) based on a quantitative descriptive approach using the PRISM protocol, including the identification, screening, eligibility, and included stages. The results of the SLR research show that research related to the analysis of mathematical critical thinking skills with a qualitative approach was most published in 2021 and 2022. Most studies are carried out at the junior high school level with the research subjects of 7th and 8th graders in the branch of algebraic mathematics. The Java region dominates research on mathematical critical thinking skills with a qualitative approach of 73%, most widely published in Sinta 4 indexed journals. The indicators of critical thinking skills that students haven’t mastered were providing arguments or reasons in answering and drawing conclusions appropriately according to the context of the problem.